Teaching the profession ethics course and its impact on joining the labor market and raising the level of work performance in organizations: A study of its application to students of community colleges at King Khalid University - Mohamed, Reda Abdelfattah Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2022)
The main objective of the research lies in clarifying the relationship between the study and application of the professional ethics course and raising the performance level of workers in work organizations. In order to achieve the goal of the study, the descriptive analytical approach was used for all of the community's 102 vocabulary items. The study reached several results, the most important of which are: There is a significant correlation relationship with a statistical significance of 64.4% at the level of morality 0.05 between studying the profession ethics course and joining the labor market and raising the level of work performance in organizations from the point of view of graduates who joined the labor market, It also resulted in a positive correlation with a statistical significance of 61.8% at a significance level of 0.05 between the study of the professional ethics course and the promotion of work values ​​in organizations. It also found a statistically significant correlation of 57.2% at the level of significance of 0.05 between ethical standards and controls and employee performance in business organizations. The study recommended the necessity of including the profession ethics course in the various stages of education so that the student is aware of these ethics and their importance before practicing them in the profession to which he joins.
Keywords: ethics; professional ethics; professional ethics course; job performance